Health Care Seeking Behavior among Older Patients with Type II Diabetes Mellitus - Rungnoei, Nongnaphat; Kruttakart, Siriporn; Meebunmak, Yaowaluck; Buneng, Nongkharn; Wachirarattanaphongmethee, Numphon (Journal of Health Science of Thailand, 2020)
This qualitative research aimed to explore health care seeking behavior and related factors of the older patients with type II diabetes mellitus receiving health care service at a diabetic clinic in community hospital. Kleinman’s explanatory model of illness and Orem’s self-care theory were used to guide the study. Twenty-nine older patients participated in this study through purposive sampling. Data were collected using in-depth interview and analyzed using content analysis. The results revealed that explanation of diabetes and health care seeking behavior were strongly influenced by social and cultural context. The older adults described their illness by exploring etiology and assessing severity of diabetes on the basis of discomforting symptoms and level of blood sugar. Every patient always used popular sector included self-care, and consulting family or neighbor before seeking care from other sectors including professional and folk sectors. They used more than one sector at the same time, and switched in among two or three sectors. Factors influencing health-seeking behavior included: 1) client factors such as explanation of illness, knowledge about diabetes, health belief, communication and seeking information skills, treatment experience, and family advice, neighbor, social network; and 2) healthcare factors such as quality of health care, health team members, distance from their home to health care setting, and costs. The results of the study provide better understanding of older patients with type II diabetes mellitus experience and their decision-making process of seeking treatment, and information for developing the health care system for the older adults.